Anti-inflammatory effects of guggulsterone on murine macrophage by inhibiting LPS-induced inflammatory cytokines in NF-κB signaling pathway - Zhang JH; Shangguan ZS; Chen C; Zhang HJ; Lin Y (Dove Medical Press, 2016)
Jin-Hua Zhang,1,2,* Zhao-Shui Shangguan,3,* Chao Chen,4 Hui-Jie Zhang,4 Yi Lin1 1College of Chemical Engineering, Huaqiao University, 2Department of Pharmacy, Xiamen Medical College, 3Central Laboratory, The First Affiliated Hospital of Xiamen University, 4Xiamen Diabetes Institute, The First Affiliated Hospital of Xiamen University, Xiamen, People’s Republic of China *These authors contributed equally to this work Abstract: The present study was aimed to investigate the effects of guggulsterone (GS) on proinflammatory responses as well as the underlying molecular mechanisms in macrophage upon lipopolysaccharide (LPS) stimulation. Effects of GS on viability of Raw264.7 cells were examined using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. Real-time polymerase chain reaction (PCR) was employed to examine the mRNA expression of cytokines, including interleukin 1β (IL-1β), tumor necrosis factor-alpha (TNF-α), and inducible nitric oxide synthase (iNOS). Phosphorylations of extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), p38 mitogen-activated protein kinases (p38), and inhibitor of nuclear factor kappaB (IκB) were determined using immunoblotting. The results revealed that GS was not toxic to Raw264.7 cells at designated concentrations. We demonstrated that GS significantly suppressed the elevated mRNA expression of proinflammatory cytokines, including IL-1β, TNF-α, and iNOS in a dose-dependent manner. GS treatment reduced the level of IκB phosphorylation in LPS-stimulated macrophages in a dose-dependent manner. Use of BAY 11-7082, an inhibitor of nuclear factor-kappaB (NF-κB), led to significantly suppressing effects on IL-1β and TNF-α expression similar as that of GS-treated cells. Our findings suggest that GS possesses anti-inflammatory activity, which may be attributed to downregulation of iNOS and inhibition of NF-κB activity in LPS-stimulated Raw264.7 cells. Keywords: Anti-inflammatory effects, guggulsterone, lipopolysaccharides, NF-κB, IL-1β, TNF-α